2015
DOI: 10.1097/aog.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

Detection Rates for Aneuploidy by First-Trimester and Sequential Screening

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 20 publications
(29 reference statements)
1
30
0
Order By: Relevance
“…Though seminal studies (eg, the FaSTER Trial) have characterized performance of non‐DNA screening for trisomy 21, herein we use Baer et al as our reference for non‐DNA screening performance because it reports sensitivity results for T13, T18, and T21, plus it involved greater than 10x more patients than the FaSTER Trial, greater than 90% of whom received integrated screening. Non‐DNA screening sensitivity for T21 and T18 was 92.9% and 93.2%, respectively, but together with the specificities (96.0% for T21, 99.6% for T18, calculated from Tables 2 and 3 in), the positive predictive values (PPV) for these trisomies are lackluster: 6.2% for T21 and 14.8% for T18 (calculated from Tables 2 and 3 in). For confirmed T13 cases, non‐DNA screening returned abnormal results in 80.4% of patients, making this number the effective sensitivity; however, because non‐DNA screening does not specifically identify T13 as the source of abnormality, specificity and PPV cannot be directly calculated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though seminal studies (eg, the FaSTER Trial) have characterized performance of non‐DNA screening for trisomy 21, herein we use Baer et al as our reference for non‐DNA screening performance because it reports sensitivity results for T13, T18, and T21, plus it involved greater than 10x more patients than the FaSTER Trial, greater than 90% of whom received integrated screening. Non‐DNA screening sensitivity for T21 and T18 was 92.9% and 93.2%, respectively, but together with the specificities (96.0% for T21, 99.6% for T18, calculated from Tables 2 and 3 in), the positive predictive values (PPV) for these trisomies are lackluster: 6.2% for T21 and 14.8% for T18 (calculated from Tables 2 and 3 in). For confirmed T13 cases, non‐DNA screening returned abnormal results in 80.4% of patients, making this number the effective sensitivity; however, because non‐DNA screening does not specifically identify T13 as the source of abnormality, specificity and PPV cannot be directly calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Each year in the United States, millions of pregnant women undergo screening to detect fetal aneuploidy on chromosomes 13, 18, and 21. Depending on the tested population, the reported collective incidence of fetal trisomy on these chromosomes ranges from approximately 1 in 100 (1,2) to 1 in 250 . While some women opt for definitive diagnosis via chorionic villus sampling (CVS) or amniocentesis (these procedures are the recommended follow‐up for all screening modalities), these invasive procedures carry a risk of pregnancy loss (medical societies report an estimated rate of 0.1%‐0.3%), and in the case of amniocentesis, patients are tested relatively late in pregnancy (typically 15‐ to 20‐week gestation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are further categorized as “Increased Risk or Screen Positive” or “Decreased Risk or Screen Negative” by the performing laboratory based on laboratory cut‐offs. Screen positive rate for each of the discussed serum screens is 5% (Baer et al, ). Screen positive rate does increase with increasing maternal age (Muller, Thalabard, Ngo, & Dommergues, ).…”
Section: Screening Testsmentioning
confidence: 99%
“…However, a large retrospective cohort study of over 450,000 women in California participating in a state-wide prenatal screening program who received first trimester screening, second trimester screening, or both in an integrated risk assessment demonstrated that the program achieved high detection rates for trisomy 21 of 92%, for trisomy 18 of 93.2%, and for trisomy 13 of 80.4% while also detecting 80% of all chromosome abnormalities (including other trisomies, monosomy, translocations, additions, duplications, inversions, rings, polyploidy, triploidy, and other chromosome abnormalities). 64 Another study evaluated how many chromosome abnormalities were detected by diagnostic testing as compared with cfDNA screening among women who were identified as screen-positive by traditional screening. Over 1.3 million patients were screened in a state-wide screening program, and 68,990 (5.2%) were screen-positive.…”
Section: Complexities and Challenges Of Clinical Implementationmentioning
confidence: 99%